Hubungan antara Perhatian Orang Tua dengan Motivasi Belajar Siswa Kelas IV - Rahayu, Shinta Dwi; Kirani, Della Nur; Ulhaq, Dhiya; Rahmawati, Halizah; Nugraheni, Eva Dwi; Nugraheni, Anggun; Sukardi, Rendi Restiana; Yuniarti, Yeni (Education and Development Research, 2023)
Abstract: Parents' attention to children has a relationship with the psychology of a child which later also makes it possible to motivate children in learning. This research was conducted with the aim of examining the effect of parental attention on the learning motivation of 4th grade elementary school students in an elementary school in the Yogyakarta region. Conducted with the type of descriptive research with a correlation approach. In this study the population used was all fourth grade students in one of the elementary schools in the Yogyakarta area. Using three ways of data collection in the form of observation, interviews, and filling out questionnaires. Based on the results of the study, the results showed that there was a relationship between the variables of parental attention and the learning motivation of fourth grade students. This is evidenced by a significant value of 0.009 less than 0.05. The relationship that occurs between the two variables is in the low category, as evidenced by the Pearson correlation value of 0.35. Thus, the parental attention variable with the learning motivation variable has a correlation with a low degree of relationship and a positive relationship. Abstrak: Perhatian orang tua kepada anak memiliki keterkaitan dengan psikologi seorang anak yang nantinya juga memungkinkan untuk dapat motivasi anak dalam belajar. Penelitian ini dilakukan dengan tujuan untuk menguji pengaruh perhatian orang tua terhadap motivasi belajar siswa kelas 4 SD di salah satu SD di wilayah Yogyakarta. Dilakukan dengan jenis penelitian deskriptif dengan pendekatan korelasi. Pada penelitian ini populasi yang digunakan adalah seluruh siswa kelas IV di salah satu SD di wilayah Yogyakarta. Menggunakan tiga cara pengambilan data berupa observasi, wawancara, dan pengisian kuesioner. Berdasarkan hasil penelitian, didapatkan hasil terdapat keterkaitan antara variabel perhatian orang tua dengan motivasi belajar siswa kelas IV. Hal tersebut dibuktikan dengan nilai yang signifikan yaitu 0,009 kurang dari 0,05. Hubungan yang terjadi antara kedua variabel termasuk kategori rendah, dibuktikan dengan nilai pearson correlation sebesar 0,35. Dengan demikian, variabel perhatian orang tua dengan variabel motivasi belajar memiliki korelasi dengan derajat hubungan rendah dan bentuk hubungannya positif.